STUDIES ON THE OCCURRENCE AND SEASONAL ABUNDANCE OF AQUATIC COLEOPTERA IN RELATION TO SOME PHYSICOCHEMICAL PARAMETERS OF WATER OF GHARANA WETLAND RESERVE JAMMU (J AND K) - J. S. TARA; RAMNIK KOUR; SUNIL SHARMA (The Bioscan, 2011)
The present study was aimed to record the occurrence and abundance of aquatic beetles (Order: Coleoptera) and physicochemical factors of water of Gharana wet land. Specimens were collected from September, 2008 to August, 2009 with pond net. A total of 11 aquatic beetle species belonging to 03 families viz. Hydrophilidae, Dytiscidae and Staphylinidae were collected. Out of these 03 families the most abundant family was Dytiscidae (56%) followed by Hydrophilidae (40%) and Staphylinidae (4%). Physicochemical parameters like water and air temperature, pH, dissolved oxygen (DO) and free carbondioxide (FCO2 ) were also measured.